Lumbar transcutaneous electrical nerve stimulation to improve exercise performance in COPD patients. Issue 6 (12th December 2019) - Bonnevie, Tristan; Gravier, Francis-Edouard; Prieur, Guillaume; Combret, Yann; Debeaumont, David; Patout, Maxime; Lamia, Bouchra; Muir, Jean-François; Médrinal, Clement; Cuvelier, Antoine
Muscle group III (Aδ fibres) and IV (C fibres) sensory afferents are involved in the cardiorespiratory adaptation to exercise [1, 2]. Their inhibition with intrathecal fentanyl in the dorsal horn of the spinal cord to block their cortical projections decreases high-intensity constant workload endurance performance in healthy athlete subjects because of a blunted cardiorespiratory response to exercise. In this condition with high metabolic demand, any decrease in ventilation or haemodynamics would compromise performance because of a nearly maximal solicitation without any possibility for a compensatory strategy. In contrast, Gagnon et al . [3] have published that the use of spinal anaesthesia with fentanyl with the goal of inhibiting muscle group III and IV fibres in chronic obstructive pulmonary disease (COPD) patients improved dyspnoea and endurance capacity. This improvement was due to the blunted ventilatory response to exercise which improved physiological dead space, ventilatory efficiency and in turn, dyspnoea. Moreover, at this relatively lower external workload compared with healthy subjects, cardiac output and peripheral oxygen extraction were not maximal and any mitigation in cardiac output (if any) would be overcome by an increase in peripheral muscle oxygen extraction [3]. High-frequency or low-frequency transcutaneous electrical nerve stimulation (TENS) provide a less invasive alternative which activates opioid receptors, especially those located in the dorsal horn of the spinal cord [1, 4, 5]. This approach deserves to be studied during exercise and over a course of pulmonary rehabilitation in these patients. We performed a randomised double-blind study (clinicaltrials.gov NCT03312322) to assess whether high-frequency or low-frequency lumbar TENS could improve endurance exercise capacity in patients with COPD. Secondary objectives were to assess the influence of lumbar TENS on perceived exertion, ventilatory pattern and muscle oxygenation. We hypothesised that endurance capacity would be improved with lumbar TENS due to a blunted response in exercise ventilation, which would contribute to improve ventilatory efficacy and reduce exercise dyspnoea. Conversely, we hypothesised that any mitigation in cardiac output (if any) would be compensated by an increase in peripheral muscular oxygen extraction. Lumbar transcutaneous electrical nerve stimulation aimed to block muscle group III–IV sensory afferents does not improve endurance exercise capacity in patients with COPD http://bit.ly/2lZr6Mt